A 40‐year chronology of the vulnerability of spinetail devil ray (Mobula mobular) to eastern Pacific tuna fisheries and options for future conservation and management. Issue 10 (10th August 2021) - Griffiths, Shane P.; Lezama‐Ochoa, Nerea
Abstract: Tuna fisheries are among the largest and most valuable fisheries in the world, but most interact with many non‐target species, including several of high conservation importance. The spinetail devil ray ( Mobula mobular ) – listed as 'Endangered' on the IUCN Red List of Threatened Species – is a commonly discarded bycatch species, particularly in the eastern Pacific Ocean, yet insufficient data exist to undertake a traditional population assessment. A new ecological risk assessment approach designed for data‐limited settings – Ecological Assessment of the Sustainable Impacts of Fisheries (EASI‐Fish) – was used to reconstruct the historical vulnerability status of M. mobular and to simulate potential changes in its status under 45 hypothetical conservation and management measures. These involved various temporal closures of the eastern Pacific Ocean tuna fishery, decreasing post‐capture mortality by improved handling and release practices, and combinations of the two. The species was classified as 'Least Vulnerable' between 1979 and 1993, but became 'Most Vulnerable' from 1994, which coincided with a rapid spatial expansion of the industrial purse‐seine fishery, and especially from 2011 following the rapid increase in the number of sets made on floating objects. Simulating the conservation and management measures in place in 2018 revealed that 31 of the 45 scenarios resulted in a change in classification of the species to 'Least Vulnerable', which primarily involved a reduction of post‐capture mortality by as little as 20%. It is fortuitous in that education of fishers to implement appropriate best handling and release practices is simpler, more rapid and more cost‐effective than the implementation of fishery closures or gear modifications, which can be expensive and complex to implement and monitor and will probably result in substantial reduction in the catches of target species.